Survivability and failure risks of steel frame structures: conceptual framework - Chichulina, Kseniia; Chichulin, Chichulin (Academic journal Industrial Machine Building Civil Engineering, 2019)
The article considers the concept of "survivability" of steel frame structures and defines its features. In the design of steelframes there is a need to reserve the main load-bearing structures to prevent progressive destruction. With the possible destructionof any individual element, the entire object or its most critical part must remain operational. The degree of damageto the system in case of failure of an individual element is determined. The main prerequisites for prevention of destruction inemergency situations, in particular, the calculation of the increase in carrying capacity. The approaches to determining therisks of failure and strengthening of steel frame elements are considered.
Keywords: survivability; destruction; redundancy; risk; damage